2020
DOI: 10.2174/1389557520666200621182717
|View full text |Cite
|
Sign up to set email alerts
|

Association of Micro RNA and Postoperative Cognitive Dysfunction: A Review

Abstract: : Postoperative Cognitive Dysfunction (POCD) refers to the condition of neurocognitive decline following a surgery in a cognitive and sensory manner. There are several risk factors, which may be life-threatening for this condition. Neuropsychological assessment of this condition is very important. In the present review, we discuss the association of apolipoprotein epsilon 4 (APOE ε4) and few miRNAs with POCD, and highlight the clinical importance for prognosis, diagnosis and treatment of POCD. Microarray is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Gene expression and protein production, which peak and trough according to the time of day, are regulated at the molecular level. This is accomplished by using two transcription-translation oscillator loops that can up-regulate and down-regulate gene expression in the nucleus and counter-regulate one another, resulting in the 24-h cycle ( 45 – 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression and protein production, which peak and trough according to the time of day, are regulated at the molecular level. This is accomplished by using two transcription-translation oscillator loops that can up-regulate and down-regulate gene expression in the nucleus and counter-regulate one another, resulting in the 24-h cycle ( 45 – 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…As in psychiatric dysfunctions such as schizophrenia (Xu et al, 2013), deregulation of miRNAs is involved in neurodegenerative abnormalities such as Parkinson's disease (PD) and AD as well (Esteller, 2011). Previous studies have reported a significant correlation that supports the role of miRNAs in POCD (Yu et al, 2015;Wei et al, 2017;Chen et al, 2019;Yazit et al, 2020). Salmena et al (2011) proposed the ceRNA hypothesis, suggesting that circRNAs interact with miRNAs to modulate gene expression at the transcriptional or posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, additional diseases and poor basal functional status of elderly patients lead to an increased incidence of POCD (3). As previously reported, the prevalence of POCD ranged from 25 to 40% among elderly patients (4). POCD is a neurological dysfunction, characterized by the continuous decline of cognitive performance after surgical anesthesia, including disturbances in consciousness, orientation, thinking, memory, and executive function.…”
Section: Introductionmentioning
confidence: 91%